Prioritizing Fetal Structural Abnormalities Over Risk for Pre-Eclampsia and Fetal Growth Restriction in the 20-24 Gestation Week Assessment in India: Missing the Woods for the Trees? - Choorakuttil, Rijo Mathew; Satarkar, Shilpa R; Sharma, Lalit K.; Gupta, Anjali; Baghel, Akanksha; Nirmalan, Praveen K. (Indian Journal of Radiology and Imaging, 2022)
Aim To compare the magnitude of fetuses with congenital anomalies, pregnant women identified at high risk for preterm pre-eclampsia (PE) or with preterm PE, and with early fetal growth restriction (FGR) or high risk for FGR at the second trimester assessment at 20 to 24 weeks of gestation.Methods A standardized trimester-specific protocol that included clinical and demographic details, fetal biometry, estimated fetal weight (EFW), fetal abdominal circumference (FAC), mean arterial blood pressure and fetal Doppler studies was used to identify high risk for preterm PE and FGR. The Targeted Imaging for Fetal Anomalies (TIFFA) scan was used to identify congenital anomalies. In addition, 95% confidence intervals of the point estimates were derived, and the p-value was estimated to assess the statistical significance of the difference in proportions.Results Analysis of the data of 4,572 pregnant women screened between 20 and 24 gestation weeks showed a significantly lower prevalence (p < 0.001) of congenital abnormalities (3.81%) compared to women diagnosed with early PE (2.71%) or with a high risk for PE (4.00%) and women (6.80%) with early FGR or at higher risk for fetal growth restriction with both EFW and FAC < 10th percentile.Conclusion The data on prevalence from Samrakshan show that the second-trimester assessment of pregnant women in India must expand its scope from the TIFFA scan to also focus on screening to identify women at high risk for preterm PE and FGR.
Keywords: fetal abnormality; fetal growth restriction; preeclampsia; second-trimester ultrasound; ultrasound